THE ROLE OF CLEAN ENERGY IN THE ENERGY TRANSFORMATION IN EASTERN EUROPE - Mysak, Pavlo (European Science, 2024)
The ongoing transformation of the power sector in Eastern European countries has been influenced by various factors.This study analyzes the determinants of energy transformation in the EU, focusing on the role and significance of clean generation technolo